2008
DOI: 10.1002/biot.200800021
|View full text |Cite
|
Sign up to set email alerts
|

Direct plant gene delivery with a poly(amidoamine) dendrimer

Abstract: Plant gene delivery is challenging due to the presence of plant cell walls. Conventional means such as Agrobacterium infection, biolistic particle bombardment, electroporation, or polyethylene glycol attachment are often characterized by high cost, labor extensiveness, and a significant perturbation to the growth of cells. We have succeeded in delivering GFP-encoding plasmid DNA to turfgrass cells using poly(amidoamine) dendrimers. Our new scheme utilizes the physiochemical properties as well as the nanosize o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…However, protoplast-based transformation methods hold disadvantages in that the viability of the protoplasts and their ability to divide are strongly reduced by the chemicals that are applied to disorganize the cell wall. For this reason, recent studies have focused on intact plant cells; it was found to that they are able to achieve endocytosis to directly internalize single-walled carbon nanotubes (CNTs), CdSe/ZnS QDs, or poly (amidoamine) dendrimer from the extracellular environment [14][15][16][17][18]. Other work showed that multi-walled CNTs with attached cellulose are also able to penetrate the cell wall, and transport intracellularly through cellulose-inducing nanoholes [19].…”
mentioning
confidence: 99%
“…However, protoplast-based transformation methods hold disadvantages in that the viability of the protoplasts and their ability to divide are strongly reduced by the chemicals that are applied to disorganize the cell wall. For this reason, recent studies have focused on intact plant cells; it was found to that they are able to achieve endocytosis to directly internalize single-walled carbon nanotubes (CNTs), CdSe/ZnS QDs, or poly (amidoamine) dendrimer from the extracellular environment [14][15][16][17][18]. Other work showed that multi-walled CNTs with attached cellulose are also able to penetrate the cell wall, and transport intracellularly through cellulose-inducing nanoholes [19].…”
mentioning
confidence: 99%
“…Such conditions will facilitate the removal of gas hydrate blockages in the oil pipeline. Our study can also be applied to the general case of loading hydrophobic molecules onto branched polymers, such as encapsulating molecules inside a dendrimer for cell trafficking [31,32] and gene delivery [33]. Another extension from this research lies in our fundamental understanding of the diffusion and reptation of nonlinear polymers [34,35].…”
Section: Resultsmentioning
confidence: 94%
“…In an another paper Martin-Ortigosa et al [295] reported that the biolistic delivery of mesoporous SiO 2 -based nanomaterials can be improved by increasing the density of mesoporous SiO 2 -based NP through Au plating, and enhancement of the NP-mediated DNA delivery can be obtained using DNA-coating protocol based on calcium chloride and spermidine for mesoporous SiO 2 NPs and Au nanorods. Nanosized poly(amidoamine) dendrimer was used for direct and non-invasive delivery of green fluorescent protein-encoding plasmid DNA to turfgrass cells by Pasupathy et al [296]. Kogure [297] reported about development of a novel artificial gene delivery system -multifunctional envelope-type nano device for gene therapy.…”
Section: Dna and Gene Delivery Using Nanoparticlesmentioning
confidence: 99%